# 5_5 - Chapter 5 Exponential and Logarithmic Functions 5.5...

This preview shows pages 1–4. Sign up to view the full content.

Chapter 5 694 Exponential and Logarithmic Functions 5.5 Properties of Logarithms 1. sum 2. 7 3. r log a M 4. False 5. False 6. True 7. log 3 3 71 = 71 8. log 2 2 - 13 = - 13 9. ln e - 4 =- 4 10. ln e 2 = 2 11. 2 log 2 7 = 7 12. e ln8 = 8 13. log 8 2 + log 8 4 = log 8 4 2 ( 29 = log 8 8 = 1 14. log 6 9 + log 6 4 = log 6 9 4 ( 29 = log 6 36 = log 6 6 2 = 2 15. log 6 18 - log 6 3 = log 6 18 3 = log 6 6 = 1 16. log 8 16 - log 8 2 = log 8 16 2 = log 8 8 = 1 17. log 2 6 log 6 4 = log 6 4 log 2 6 = log 6 2 2 ( 29 log 2 6 = log 6 2 ( 29 2log 2 6 = log 6 2 ( 29 log 2 6 2 = log 6 6 2 = 2 18. log 3 8 log 8 9 = log 8 9 log 3 8 = log 8 3 2 ( 29 log 3 8 = log 8 3 ( 29 2log 3 8 = log 8 3 ( 29 log 3 8 2 = log 8 8 2 = 2 19. 3 log 3 5 - log 3 4 = 3 log 3 5 4 = 5 4 20. 5 log 5 6 + log 5 7 = 5 log 5 6 7 ( 29 = 6 7 = 42

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Section 5.5 Properties of Logarithms 695 21. e log e 2 16 22. e log e 2 9 Simplify the exponent. Let a = log e 2 16, then e 2 ( 29 a = 16. e 2 a = 16 e 2 a = 4 2 e 2 a ( 29 1/2 = 4 2 ( 29 1/2 e a = 4 a = ln4 Thus, e log e 2 16 = e ln4 = 4. Simplify the exponent. Let a = log e 2 9, then e 2 ( 29 a = 9. e 2 a = 9 e 2 a = 3 2 e 2 a ( 29 1/2 = 3 2 ( 29 1/2 e a = 3 a = ln3 Thus, e log e 2 9 = e ln3 = 3. 23. ln6 = ln(3 2) = ln3 + ln2 = b + a 24. ln 2 3 = ln2 - ln3 = a - b 25. ln1.5 = ln 3 2 = ln3 - ln2 = b - a 26. ln0.5 = ln 1 2 = ln1 - ln2 = 0 - a = - a 27. ln8 = ln2 3 = 3 ln2 = 3 a 28. ln27 = ln3 3 = 3 ln3 = 3 b 29. ln 6 5 = ln6 1/5 = 1 5 ln6 = 1 5 ln 2 3 ( 29 = 1 5 ln2 + ln3 ( 29 = 1 5 a + b ( 29 30. ln 2 3 4 = ln 2 3 1/4 = 1 4 ln 2 3 = 1 4 ln2 - ln3 ( 29 = 1 4 a - b ( 29 31. log 5 25 x ( 29 = log 5 25 + log 5 x = 2 + log 5 x 32. log 3 x 9 = log 3 x - log 3 9 = log 3 x - 2 33. log 2 z 3 = 3log 2 z 34. log 7 x 5 = 5log 7 x 35. ln ex ( 29 = ln e + ln x = 1 + ln x 36. ln e x = ln e - ln x = 1 - ln x 37. ln xe x ( 29 = ln x + ln e x = ln x + x 38. ln x e x  = ln x - ln e x = ln x - x 39. log a u 2 v 3 ( 29 = log a u 2 + log a v 3 = 2log a u + 3log a v 40. log 2 a b 2  = log 2 a - log 2 b 2 = log 2 a - 2log 2 b
Chapter 5 Exponential and Logarithmic Functions 696 41. ln x 2 1 - x ( 29 = ln x 2 + ln 1 - x = ln x 2 + ln(1 - x ) 1/2 = 2ln x + 1 2 ln(1 - x ) 42. ln x 1 + x 2 ( 29 = ln x + ln 1 + x 2 = ln x + ln(1 + x 2 ) 1/2 = ln x + 1 2 ln(1 + x 2 ) 43. log 2 x 3 x - 3 = log 2 x 3 - log 2 ( x - 3) = 3log 2 x - log 2 ( x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This homework help was uploaded on 04/07/2008 for the course MAC 1105 taught by Professor Any during the Spring '08 term at FIU.

### Page1 / 11

5_5 - Chapter 5 Exponential and Logarithmic Functions 5.5...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online